Effect of Serum Trace Elements in Hand Eczema Patients in Sulaimani Province: A Case-Control Study - Hamad, Nasrin Sulaiman; Tofiq, Diary Ibrahim (Technium BioChemMed, 2021)
Atopic dermatitis (AD) pathophysiology incorporates a complex interaction exchange of brokenness of the immune system, science, and environmental factors. It is notable that nutritional status is significant for an appropriately working immune system, which prompts a furiously contested inquiry regarding the part of dietary variables in the pathogenesis of AD. Minor components are micronutrients found in the body in restricted sums, and are a vital factor in keeping up a healthy immune system. In this investigation, we examined the degrees of to the (Mg, Ti, Mn, Fe, Zn, Cd, Cr, Cu, Ni, Pb, Al, and Se) in the serum of the AD understanding we contrasted our discoveries and those of a healthy group. The investigation populace included 60 AD patients and 50 controls from the center of skin feeding in Slemani, private skin clinic, and clinical center of many concrete production lines. We performed minor components estimation in the serum tests acquired from the two patients and the control group utilizing (ICP-MS). We found a significant difference (P<0.05) of Mg, Mn, Fe, Zn, Cd, Cr, Cu, Ni, Pb, and Se in the serum levels of the AD patients in comparison to the control group, and showed a reduction difference for the Mg, Ti, Mn, Fe, Zn, and Cd (35.576±4.67, 299.989±59.64, 133.471±80.17, 3316.234±1132.78, 289.507±61.23, 28.304±35.50, and 18.509±6.703) correspondingly, while for the Al, Cr, Ni, Cu, Se and Pb (2599.950±559.57, 45.342±17.69, 463.838±626.69, 1524.524±547.82, 31.775±18.11 and 180.717±127.47) respectively, revealed significant increasing. Assessment of the zinc and lead serum levels in the dermatitis populace might be valuable, and further examination of their immunological capacity in pathogenesis and treatment of skin inflammation is required.